Coupled SWAT-MODFLOW model for large-scale mixed agro-urban river basins. (May 2019) - Aliyari, Fatemeh; Bailey, Ryan T.; Tasdighi, Ali; Dozier, André; Arabi, Mazdak; Zeiler, Kurt
Abstract: Within river basins, water resources competition often exists between agricultural, municipal and industrial sectors, particularly in semi-arid regions where surface water and groundwater are managed conjunctively to sustain urban areas and food production. There is a need for physically-based modeling tools to assist with identifying successful water management strategies in these basins. This paper presents an updated version of SWAT-MODFLOW that allows application to large agro-urban river basins in semi-arid regions. Code changes include linkage between MODFLOW pumping cells and SWAT HRUs for groundwater irrigation, joint groundwater and surface water irrigation routines, and the use of MODFLOW-PSB to handle the large array of groundwater sources/sinks that exist in a highly managed river basin. Model performance is demonstrated for the 72, 000 km 2 South Platte River Basin, Colorado, USA. The model can be used in agro-urban river basins worldwide to assess water resources supply under a variety of scenarios. Highlights: Updated SWAT-MODFLOW code can be used for large agro-urban river basins. The model includes all major water transfer pathways for managed river basins. The model links MODFLOW pumping to SWAT groundwater irrigation. The model is tested in a 72, 000 km 2 river basin in Colorado, USA.